New energy electric vehicle motor shaft and preparation process thereof
By using materials such as high-strength matrix alloys and advanced processes, new energy electric vehicle motor shafts with high mechanical properties and corrosion resistance were prepared, which solved the problem of insufficient performance of the motor shaft in high load and high temperature environments, and significantly improved its Lifespan and reliability.
Patent Information
- Application Number
- CN202411324086.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-13
AI Technical Summary
When facing high load, complex working conditions and high temperature environments, existing motor shafts show insufficient strength, poor toughness and low corrosion resistance, resulting in shortened service life and reduced reliability, which cannot meet the high-performance needs of new energy vehicles.
Using high-strength matrix alloys, titanium alloys, carbon nanotubes, rare earth elements, silicon nitride ceramic particles and other materials, combined with vacuum arc furnace smelting, precision forging, precision heat treatment and ion implantation technology, we can prepare higher mechanical properties and corrosion resistance Capacity of motor shaft and surface plating to improve electrochemical performance.
It significantly improves the mechanical properties, corrosion resistance and high temperature stability of the motor shaft, extends the service life, and enhances the reliability under complex working conditions and long-term stable operation ability under high temperature environments.
Smart Images

Figure CN119120976A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of motor shafts, and in particular to a motor shaft for a new energy electric vehicle and a preparation process thereof. Background Art
[0002] With the enhancement of global environmental awareness and the intensification of the energy crisis, new energy vehicles, especially electric vehicles, have become an important direction for the development of the modern automobile industry. New energy electric vehicles have received widespread attention and rapid development with their advantages of zero emissions, low noise and high energy efficiency. The core technologies of electric vehicles include battery technology, motor technology and control system technology, which together determine the performance and reliability of electric vehicles. In new energy electric vehicles, the motor is one of the core components. It is not only responsible for converting electrical energy into mechanical energy to drive the vehicle, but also involves energy recovery, acceleration performance, smooth driving experience and other aspects. The performance of the motor directly affects the power output, energy efficiency and cruising range of electric vehicles. Therefore, high-performance motors are crucial for new energy electric vehicles. The motor shaft is a key component inside the motor, which plays the role of transmitting torque and supporting the rotor. During the operation of the motor, the motor shaft needs to withstand huge mechanical stress and speed, and also face complex working environments such as high temperature, high humidity and vibration. The material and manufacturing process of the motor shaft determine its strength, stiffness, wear resistance and corrosion resistance, which in turn affects the performance and life of the entire motor.
[0003] However, with the development and application of new energy vehicles, higher requirements are placed on the mechanical properties of motor shafts; First, existing motor shafts often show problems of insufficient strength and toughness when facing higher loads and complex working conditions, resulting in a shortened shaft life and reduced reliability. Traditional materials are prone to fatigue fracture and deformation when facing high load impact and long-term use, and cannot meet the needs of high-performance electric vehicles. Secondly, during the use of new energy vehicles, the motor shaft is often exposed to corrosive environments such as moisture and salt spray. The corrosion resistance of traditional materials and processes is insufficient, which makes the motor shaft susceptible to corrosion during use and the surface oxide layer peels off, which in turn affects the mechanical properties and service life. The corrosion problem not only shortens the life of the motor shaft, but also increases maintenance costs, affecting the overall performance and reliability of new energy vehicles; Finally, new energy vehicles work for a long time under high temperature conditions. The durability of traditional heat-resistant steel in high temperature environment is insufficient, and it is prone to high temperature creep and strength reduction problems, resulting in poor stability and durability of the motor shaft under high temperature conditions. In a high temperature environment above 600°C, the tensile strength and durability of traditional materials are significantly reduced, which cannot meet the long-term operation requirements of new energy vehicles under high temperature conditions. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a new energy electric vehicle motor shaft and a preparation process thereof, which solves the problem that the motor shaft cannot adapt to complex working conditions.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: a new energy electric vehicle motor shaft and its preparation process, including the following component materials: 50 to 65 parts of high-strength matrix alloy, 20 to 30 parts of titanium alloy, 2 to 4 parts of carbon nanotubes, 0.34 to 0.6 parts of rare earth elements, 1.5 to 3 parts of niobium, 11 to 14 parts of silicon nitride ceramic particles, 1 to 2 parts of zirconium, 0.05 to 0.2 parts of boron, 0.1 to 0.5 parts of vanadium, 0.1 to 0.3 parts of titanium, 1 to 3 parts of nickel, and 0.5 to 1.5 parts of copper.
[0006] Preferably, the high-strength matrix alloy comprises carbon, silicon, manganese, chromium and molybdenum, and the addition ratio of carbon, silicon, manganese, chromium and molybdenum is 1:0.53:1.58:2.63:0.53.
[0007] Preferably, the rare earth elements include yttrium, neodymium, lanthanum, cerium and samarium, and the addition ratio of yttrium, neodymium, lanthanum, cerium and samarium is 5:2:1:1:1.
[0008] Preferably, the silicon nitride ceramic particles include silicon nitride, aluminum oxide, and yttrium oxide, and the addition ratio of silicon nitride, aluminum oxide, and yttrium oxide is 17:1:0.8.
[0009] A new energy electric vehicle motor shaft and a preparation process thereof, comprising the following steps: S1. Raw material preparation: prepare high-strength matrix alloy, titanium alloy 20, carbon nanotubes, rare earth elements, niobium, silicon nitride ceramic particles, zirconium, boron, vanadium, titanium, nickel, and copper; S2. Material mixing: the high-strength matrix alloy and the titanium alloy are melted in a vacuum arc furnace at a temperature of 1650°C to 1700°C for 240min to 360min, and then carbon nanotubes, rare earth elements, niobium, silicon nitride ceramic particles, zirconium, boron, vanadium, titanium, nickel and copper are added in sequence, and the melting is continued for 30min to 45min to obtain a metal solution; S3, forging: pour the molten metal into the mold and cool it into a blank, then send it into a forging machine for forging for 120min to 240min, the initial forging temperature is controlled at 1250℃ to 1300℃, then the temperature of the forging machine rises to 1050℃ to 1100℃, and then forging for another 120min to 240min to obtain embryo A; S4, heat treatment: embryo A is placed in a quenching device, quenched at 950°C to 1000°C for 35min to 55min, and then placed in a cooling pool for cooling for 12min to 20min. The quenched embryo A is placed in a tempering furnace and heated to 600°C to 650°C, and tempered for 240min to 355min to obtain embryo B; S5, post-processing: Use CNC machine tools to turn and grind the heat-treated embryo B to obtain the motor shaft, and then use ion implantation technology to introduce nitrogen and carbon ions on the surface of the motor shaft, and then plate a layer of titanium aluminum nitrogen on the surface of the motor shaft. Preferably, in step S1, the vacuum degree of the vacuum arc furnace is maintained at 10^-5 Torr, and the current arc is between 150A and 200A.
[0010] Preferably, in the step S3, the pressure of the forging machine during initial forging is 535 MPa to 749 MPa, and the pressure of the forging machine during reforging is 325 MPa to 478 MPa.
[0011] Preferably, in step S5, the spindle speed of the CNC machine tool during turning is 1530RPM-2980RPM, the feed speed is 0.1mm / rev-0.3mm / rev, and the corresponding grinding speed during grinding is 30m / s-50m / s.
[0012] Preferably, in the step S5, the ion implantation technique is performed using plasma enhanced chemical vapor deposition, the implantation time is 2 hours to 3 hours, and the implantation temperature is 400° C. to 500° C.
[0013] Preferably, in step S5, the thickness of the titanium aluminum nitrogen coating is between 3 μm and 7 μm.
[0014] The present invention provides a new energy electric vehicle motor shaft and a manufacturing process thereof. It has the following beneficial effects: 1. The present invention adds carbon nanotubes, rare earth elements, niobium and silicon nitride ceramic particles, and adopts advanced vacuum arc furnace melting, precision forging and precision heat treatment processes, so that the motor shaft can withstand higher mechanical loads, adapt to more complex working conditions, and provide more excellent mechanical properties and reliability.
[0015] 2. By introducing rare earth elements and surface coating treatment, the electrochemical performance of the motor shaft of the present invention in a corrosive environment is significantly improved, so that the motor shaft exhibits higher corrosion resistance, can maintain stable performance for a longer time in a harsh environment, and reduces the impact of corrosion on the motor shaft, thereby extending the service life and improving reliability.
[0016] 3. Through the comprehensive enhancement of multiple additives and the optimized heat treatment process, the long-term tensile strength and long-term life of the motor shaft of the present invention in a high-temperature environment are significantly improved, thereby meeting the use requirements of new energy vehicles under high-temperature conditions, ensuring its long-term stable operation in a high-temperature environment, and making it suitable for a wider range of high-temperature application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a stereogram of the present invention. DETAILED DESCRIPTION
[0018] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Example 1: Basic motor shaft preparation process Specific steps: S1. Raw material preparation: prepare high-strength matrix alloy (65 parts) and titanium alloy (25 parts); S2. Material mixing: melting the high-strength matrix alloy and the titanium alloy in a vacuum arc furnace at a temperature of 1650° C. for 240 minutes to obtain a molten metal; S3, forging: pour the molten metal into the mold and cool it into a blank, then send it to the forging machine for initial forging for 120 minutes. The initial forging temperature is controlled at 1250°C, and the temperature of the forging machine rises to 1050°C, and then forging for another 120 minutes to obtain embryo A; S4, heat treatment: embryo A is placed in a quenching device, quenched at 975°C for 45 minutes, and then placed in a cooling pool for cooling for 15 minutes. The quenched embryo A is placed in a tempering furnace and heated to 625°C for tempering for 300 minutes to obtain embryo B; S5. Post-processing: Use a CNC machine tool to turn and grind the heat-treated embryo B, with a spindle speed of 2000RPM, a feed speed of 0.2mm / rev, and a grinding speed of 40m / s. A layer of titanium aluminum nitrogen is plated on the surface of the motor shaft with a coating thickness of 5μm.
[0020] Summarize: This embodiment uses a traditional high-strength matrix alloy and a titanium alloy combination to prepare a basic motor shaft suitable for general working conditions.
[0021] Example 2: Preparation process of motor shaft with carbon nanotubes added Specific steps: S1. Raw material preparation: prepare high-strength matrix alloy (65 parts), titanium alloy (25 parts), and carbon nanotubes (4 parts); S2. Material mixing: melting the high-strength matrix alloy and titanium alloy in a vacuum arc furnace, controlling the temperature at 1650° C. for 240 minutes, adding carbon nanotubes in sequence, and continuing to melt for 30 minutes to obtain a metal solution; S3, forging: pour the molten metal into the mold and cool it into a blank, then send it to the forging machine for initial forging for 120 minutes. The initial forging temperature is controlled at 1250°C, and the temperature of the forging machine rises to 1050°C, and then forging for another 120 minutes to obtain embryo A; S4, heat treatment: embryo A is placed in a quenching device, quenched at 975°C for 45 minutes, and then placed in a cooling pool for cooling for 15 minutes. The quenched embryo A is placed in a tempering furnace and heated to 625°C for tempering for 300 minutes to obtain embryo B; S5. Post-processing: Use a CNC machine tool to turn and grind the heat-treated embryo B, with a spindle speed of 2000RPM, a feed speed of 0.2mm / rev, and a grinding speed of 40m / s. A layer of titanium aluminum nitrogen is plated on the surface of the motor shaft with a coating thickness of 5μm.
[0022] Summarize: The addition of carbon nanotubes in the basic process significantly improves the strength and wear resistance of the motor shaft, making it more suitable for use under high-load conditions.
[0023] Example 3: Preparation process of motor shaft reinforced with rare earth elements Specific steps: S1. Raw material preparation: prepare high-strength matrix alloy (65 parts), titanium alloy (25 parts), carbon nanotubes (4 parts), and rare earth elements (0.6 parts); S2. Material mixing: melting the high-strength matrix alloy and titanium alloy in a vacuum arc furnace, controlling the temperature at 1650° C. for 240 minutes, adding carbon nanotubes and rare earth elements in sequence, and continuing to melt for 30 minutes to obtain a metal solution; S3, forging: pour the molten metal into the mold and cool it into a blank, then send it to the forging machine for initial forging for 120 minutes. The initial forging temperature is controlled at 1250°C, and the temperature of the forging machine rises to 1050°C, and then forging for another 120 minutes to obtain embryo A; S4, heat treatment: embryo A is placed in a quenching device, quenched at 975°C for 45 minutes, then placed in a cooling pool for cooling for 15 minutes, and the quenched embryo A is placed in a tempering furnace and heated to 625°C for tempering for 300 minutes to obtain embryo B; S5. Post-processing: Use a CNC machine tool to turn and grind the heat-treated embryo B, with a spindle speed of 2000RPM, a feed speed of 0.2mm / rev, and a grinding speed of 40m / s. A layer of titanium aluminum nitrogen is plated on the surface of the motor shaft with a coating thickness of 5μm.
[0024] Summarize: The addition of rare earth elements in the basic process significantly improves the high temperature performance and oxidation resistance of the motor shaft, making it perform better in high temperature environments.
[0025] Example 4: Preparation process of motor shaft reinforced with silicon nitride ceramic particles Specific steps: S1. Raw material preparation: prepare high-strength matrix alloy (65 parts), titanium alloy (25 parts), carbon nanotubes (4 parts), rare earth elements (0.6 parts), and silicon nitride ceramic particles (12 parts); S2. Material mixing: melting high-strength matrix alloy and titanium alloy in a vacuum arc furnace, controlling the temperature at 1650° C. for 240 minutes, adding carbon nanotubes, rare earth elements and silicon nitride ceramic particles in sequence, and continuing melting for 30 minutes to obtain a metal solution; S3, forging: pour the molten metal into the mold and cool it into a blank, then send it to the forging machine for initial forging for 120 minutes. The initial forging temperature is controlled at 1250°C, and the temperature of the forging machine rises to 1050°C, and then forging for another 120 minutes to obtain embryo A; S4, heat treatment: embryo A is placed in a quenching device, quenched at 975°C for 45 minutes, and then placed in a cooling pool for cooling for 15 minutes. The quenched embryo A is placed in a tempering furnace and heated to 625°C for tempering for 300 minutes to obtain embryo B; S5. Post-processing: Use a CNC machine tool to turn and grind the heat-treated embryo B, with a spindle speed of 2000RPM, a feed speed of 0.2mm / rev, and a grinding speed of 40m / s. A layer of titanium aluminum nitrogen is plated on the surface of the motor shaft with a coating thickness of 5μm.
[0026] Summarize: The addition of silicon nitride ceramic particles in the basic process significantly improves the wear resistance and fatigue resistance of the motor shaft, making it more suitable for high-wear conditions.
[0027] Example 5: Preparation process of motor shaft reinforced with multiple additives Specific steps: S1. Raw material preparation: prepare high-strength matrix alloy (65 parts), titanium alloy (25 parts), carbon nanotubes (4 parts), rare earth elements (0.6 parts), silicon nitride ceramic particles (12 parts), niobium (3 parts), zirconium (2 parts), boron (0.2 parts), vanadium (0.5 parts), titanium (0.3 parts), nickel (3 parts), copper (1.5 parts); S2. Material mixing: melting high-strength matrix alloy and titanium alloy in a vacuum arc furnace, controlling the temperature at 1650° C. for 240 minutes, adding carbon nanotubes, rare earth elements, silicon nitride ceramic particles, niobium, zirconium, boron, vanadium, titanium, nickel and copper in sequence, and continuing melting for 30 minutes to obtain a metal solution; S3, forging: pour the molten metal into the mold and cool it into a blank, then send it to the forging machine for initial forging for 120 minutes. The initial forging temperature is controlled at 1250°C, and the temperature of the forging machine rises to 1050°C, and then forging for another 120 minutes to obtain embryo A; S4, heat treatment: embryo A is placed in a quenching device, quenched at 975°C for 45 minutes, and then placed in a cooling pool for cooling for 15 minutes. The quenched embryo A is placed in a tempering furnace and heated to 625°C for tempering for 300 minutes to obtain embryo B; S5. Post-processing: Use a CNC machine tool to turn and grind the heat-treated embryo B, with a spindle speed of 2000RPM, a feed speed of 0.2mm / rev, and a grinding speed of 40m / s. A layer of titanium aluminum nitrogen is plated on the surface of the motor shaft with a coating thickness of 5μm.
[0028] Summarize: This embodiment significantly improves the comprehensive performance of the motor shaft, including strength, wear resistance and high-temperature stability, through comprehensive reinforcement of multiple additives, making it adaptable to a variety of complex working conditions.
[0029] Summary: In the above five embodiments, we have demonstrated the effect of gradually adding different innovative points on improving the performance of the motor shaft. In Example 1, only traditional high-strength matrix alloys and titanium alloys are used to prepare a basic motor shaft, which is suitable for general working conditions. In Example 2, carbon nanotubes are added to the basic process, which significantly improves the strength and wear resistance of the motor shaft, making it more suitable for use under high-load conditions. In Example 3, rare earth elements are further added to the basic process, which significantly improves the high-temperature performance and oxidation resistance of the motor shaft, making it perform better in high-temperature environments. In Example 4, silicon nitride ceramic particles are added to the basic process, which significantly improves the wear resistance and fatigue resistance of the motor shaft, making it more suitable for high-wear conditions. In Example 5, a variety of additives (carbon nanotubes, rare earth elements, silicon nitride ceramic particles, etc.) are comprehensively added to significantly improve the comprehensive performance of the motor shaft, including strength, wear resistance and high-temperature stability, so that it can adapt to a variety of complex working conditions.
[0030] Test experiment: Test experimental steps: S1. Material preparation: preparing a motor shaft according to the processes of different embodiments; S2. Strength test: Use a universal material testing machine to test the maximum tensile strength; S3. Wear resistance test: Use a grinding wheel wear tester to test the amount of wear per unit time; S4. High temperature stability test: high temperature tensile test in 600℃ environment; S5. Anti-fatigue performance test: Use a rotary bending fatigue testing machine to test fatigue life.
[0031] Test data: Example Maximum tensile strength (MPa) Wear rate (g / h) High temperature tensile strength (MPa) Fatigue life (cycles) Embodiment 1 950 0.15 700 500,000 Embodiment 2 1050 0.12 750 600,000 Embodiment 3 1080 0.11 850 650,000 Embodiment 4 1100 0.09 870 700,000 Embodiment 5 1150 0.07 900 750,000 Summary: Through performance testing of five embodiments, the results show that the performance of the motor shaft is significantly improved after gradually adding different innovative points. The motor shaft of the basic process shows basic strength and wear resistance, but low high temperature stability and fatigue life. After adding carbon nanotubes, the strength and wear resistance of the motor shaft are improved. After adding rare earth elements, the high temperature performance and antioxidant ability are significantly improved. After adding silicon nitride ceramic particles, the wear resistance and fatigue resistance are significantly improved. After the comprehensive addition of multiple additives, the motor shaft shows the most excellent comprehensive performance, which can meet the needs of various complex working conditions.
[0032] Comparative experiment: Comparative experiment 1: comprehensive mechanical properties test Technical solutions of existing technology: 1. Material: traditional 45 steel; 2. Process: conventional heat treatment process, including quenching and tempering; The technical solution of the present invention: 1. Materials: high-strength matrix alloy, titanium alloy, carbon nanotubes, rare earth elements, niobium, silicon nitride ceramic particles, zirconium, boron, vanadium, titanium, nickel, copper; 2. Process: vacuum arc furnace melting, precision forging, precision heat treatment, ion implantation and surface coating treatment; Testing process: S1. Material preparation: Prepare a motor shaft sample according to the prior art and the process of the present invention; S2. Comprehensive mechanical properties test: test maximum tensile strength, yield strength and fracture toughness.
[0033] Experimental data: Example Maximum tensile strength (MPa) Yield strength(MPa) Fracture toughness(J / m²) Prior art 750 450 50 The present invention 1150 800 120 Summarize: The motor shaft of the present invention is significantly superior to the prior art in terms of comprehensive mechanical properties. Specifically, the maximum tensile strength, yield strength and fracture toughness of the present invention are significantly higher than those of traditional materials, showing more excellent mechanical properties, which indicates that the materials and processes of the present invention have significant advantages in enhancing the mechanical properties of the motor shaft.
[0034] Comparative experiment 2: Corrosion resistance test Technical solutions of existing technology: 1. Material: traditional stainless steel; 2. Process: conventional heat treatment process; The technical solution of the present invention: 1. Materials: high-strength matrix alloy, titanium alloy, carbon nanotubes, rare earth elements, niobium, silicon nitride ceramic particles, zirconium, boron, vanadium, titanium, nickel, copper; 2. Process: vacuum arc furnace melting, precision forging, precision heat treatment, ion implantation and surface coating treatment; Testing process: S1. Material preparation: Prepare a motor shaft sample according to the prior art and the process of the present invention; S2. Corrosion resistance test: Conduct electrochemical corrosion test in 3.5% NaCl solution to measure corrosion potential and corrosion current density.
[0035] Experimental data: Example Corrosion potential (V) Corrosion current density (A / cm²) Prior art -0.35 1.5×10^-6 The present invention -0.20 2.5×10^-7 Summarize: The motor shaft of the present invention is significantly superior to the prior art in terms of corrosion resistance. Specifically, the corrosion potential of the present invention is more positive, the corrosion current density is lower, and it exhibits stronger corrosion resistance, which indicates that the materials and processes of the present invention have significant advantages in enhancing the corrosion resistance of the motor shaft.
[0036] Comparative experiment three: high temperature endurance performance test Technical solutions of existing technology: 1. Material: traditional heat-resistant steel; 2. Process: conventional heat treatment process; The technical solution of the present invention: 1. Materials: high-strength matrix alloy, titanium alloy, carbon nanotubes, rare earth elements, niobium, silicon nitride ceramic particles, zirconium, boron, vanadium, titanium, nickel, copper; 2. Process: vacuum arc furnace melting, precision forging, precision heat treatment, ion implantation and surface coating treatment; Testing process: S1. Material preparation: Prepare a motor shaft sample according to the prior art and the process of the present invention; S2. High temperature endurance performance test: High temperature endurance performance test is carried out in 600℃ and 800℃ environment to measure the endurance tensile strength and endurance life.
[0037] Experimental data: Example Temperature(℃) Tensile strength at lasting (MPa) Durability (h) Prior art 600 400 1000 The present invention 600 700 2000 Prior art 800 250 500 The present invention 800 500 1500 Summarize: The motor shaft of the present invention is significantly superior to the prior art in terms of high-temperature durability. Specifically, the sustained tensile strength and sustained life of the present invention in a high-temperature environment are significantly higher than those of traditional heat-resistant steels, showing better high-temperature stability and durability, which indicates that the materials and processes of the present invention have significant advantages in enhancing the high-temperature performance and durability of the motor shaft.
[0038] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A motor shaft of a new energy electric vehicle, characterized in that: Includes the following components: 50 to 65 parts of high-strength matrix alloy, 20 to 30 parts of titanium alloy, 2 to 4 parts of carbon nanotubes, 0.34 to 0.6 parts of rare earth elements, 1.5 to 3 parts of niobium, 11 to 14 parts of silicon nitride ceramic particles, 1 to 2 parts of zirconium, 0.05 to 0.2 parts of boron, 0.1 to 0.5 parts of vanadium, 0.1 to 0.3 parts of titanium, 1 to 3 parts of nickel, and 0.5 to 1.5 parts of copper.
2. The motor shaft of a new energy electric vehicle according to claim 1, characterized in that: The high-strength matrix alloy includes carbon, silicon, manganese, chromium, and molybdenum, and the addition ratio of carbon, silicon, manganese, chromium, and molybdenum is 1:0.53:1.58:2.63:0.
53.
3. The motor shaft of a new energy electric vehicle according to claim 1, characterized in that: The rare earth elements include yttrium, neodymium, lanthanum, cerium and samarium, and the addition ratio of yttrium, neodymium, lanthanum, cerium and samarium is 5:2:1:1:
1.
4. The motor shaft of a new energy electric vehicle according to claim 1, characterized in that: The silicon nitride ceramic particles include silicon nitride, aluminum oxide, and yttrium oxide, and the addition ratio of the silicon nitride, aluminum oxide, and yttrium oxide is 17:1:0.
8.
5. A new energy electric vehicle motor shaft and its preparation process, according to the new energy electric vehicle motor shaft described in claims 1-4, characterized in that: The following steps are involved: S1. Raw material preparation: prepare high-strength matrix alloy, titanium alloy 20, carbon nanotubes, rare earth elements, niobium, silicon nitride ceramic particles, zirconium, boron, vanadium, titanium, nickel, and copper; S2. Material mixing: the high-strength matrix alloy and the titanium alloy are melted in a vacuum arc furnace at a temperature of 1650°C to 1700°C for 240min to 360min, and then carbon nanotubes, rare earth elements, niobium, silicon nitride ceramic particles, zirconium, boron, vanadium, titanium, nickel and copper are added in sequence, and the melting is continued for 30min to 45min to obtain a metal solution; S3, forging: pour the molten metal into the mold and cool it into a blank, then send it into a forging machine for forging for 120min to 240min, the initial forging temperature is controlled at 1250℃ to 1300℃, then the temperature of the forging machine rises to 1050℃ to 1100℃, and then forging for another 120min to 240min to obtain embryo A; S4, heat treatment: embryo A is placed in a quenching device, quenched at 950°C to 1000°C for 35min to 55min, and then placed in a cooling pool for cooling for 12min to 20min. The quenched embryo A is placed in a tempering furnace and heated to 600°C to 650°C, and tempered for 240min to 355min to obtain embryo B; S5. Post-processing: Use a CNC machine tool to turn and grind the heat-treated embryo B to obtain a motor shaft, then introduce nitrogen and carbon ions into the surface of the motor shaft through ion implantation technology, and then plate a layer of titanium aluminum nitrogen on the surface of the motor shaft.
6. A new energy electric vehicle motor shaft and its preparation process according to claim 5, characterized in that: In the step S1, the vacuum degree of the vacuum arc furnace is maintained at 10^-5 Torr, and the current arc is between 150A and 200A.
7. The motor shaft of a new energy electric vehicle and its preparation process according to claim 5, characterized in that: In the step S3, the pressure of the forging machine during the initial forging is 535MPa-749MPa, and the pressure of the forging machine during the reforging is 325MPa-478MPa.
8. The motor shaft of a new energy electric vehicle and its preparation process according to claim 5, characterized in that: In step S5, the spindle speed of the CNC machine tool during turning is 1530RPM-2980RPM, the feed speed is 0.1mm / rev-0.3mm / rev, and the corresponding grinding speed during grinding is 30m / s-50m / s.
9. A new energy electric vehicle motor shaft and its preparation process according to claim 5, characterized in that: In the step S5, the ion implantation technology is performed by plasma enhanced chemical vapor deposition, the implantation time is 2 hours to 3 hours, and the implantation temperature is 400° C. to 500° C.
10. A new energy electric vehicle motor shaft and its preparation process according to claim 5, characterized in that: In the step S5, the thickness of the titanium aluminum nitrogen coating is 3 μm to 7 μm.
Citation Information
Cited By
Method and system for improving NVH (Noise Vibration and Harshness) of driving shaft of pure electric vehicle based on new material application
CN120905495A
